023: INVERTING THE PYRAMID: LEARNING BY DOING RESEARCH AS A CURE TO PILOT-ISM AND ACHIEVING EFFECTIVE SCALE-UP OF E/M-HEALTH PROJECTS IN THE PHILIPPINES. (24th August 2015) - Canlas, Felipe Canlas
Abstract : Background: The Philippines' Department of Health state that "reliability of health information remains the primary challenge in health policy planning and intervention". Can electronic health recording systems help generate quality health data? Evidence is inconclusive, especially in developing countries. The research by Wireless Access for Health aims to contribute answers to this question. With over five years of experience on e-Health implementation, WAH holds one of the largest electronic patient record databases in the country. More so, WAH has become a repository of what has worked and what has not for e-Health scale-up in the Philippines. By partnering with academic institutions like the Asian Institute of Management (AIM) and New York University (NYU), WAH has made possible the conduct of data-mining and empirical research on these data. The answers we offer add light to some intriguing questions on e/m-Health implementation in the Philippines. Objectives: The research aims to answer the following claims: Use of an EMR increases time spent of health workers on consultation thereby helping improve patient care. Use of an EMR improves access to higher quality health data. Use of an EMR facilitates data analysis and utilization promoting informed decision- making leading to better health policy planning and timely health intervention. Methods: The research builds on a previous research done in 2013 using data from 39 clinics in Tarlac. Now with more than 100, updated database, and additional two years of data coming from clinics all over the country, the new research employed statistical analysis on aggregate health data reports. This was supported by secondary data-gathering techniques of content-analysis on the data generated by and researches performed independently by AIM and NYU in 2013 and 2014. Result: The research on the efficacy of the WAH-EHR in bringing forth change in local health systems confirms the results proclaimed by the first research in 2013, which are the following: that use of an EHR increased efficiency in the clinic by (a) decreasing waiting time by patient during consultations at the clinic, (b) decreasing health/patient information recording, compiling, and reporting by clinicians; and (c) increasing number of patients accommodated at the clinic over time. Result of the research also claims that use of an EHR generates and improves access to higher quality health data. Conclusion: As local e-Health systems like WAH continue to scale-up, empirical evidence enables us to document the gaps and good practices in using an EHR. Support is needed to keep initiatives like WAH going and moving for national scale-up. WAH has shown that pooling of resources by public and private sector partners is desirable if we are to make the scale up of local systems possible. Empirical evidence gathered by WAH and independent research teams support the hypothesis that WAH helped improve the quality of data recording and submission by partner clinics. Anecdotal evidence and qualitative data also suggest that clinicians now feel and work with more pride and enthusiasm. Finally, cost-benefit analysis and end-user and client interviews support the claim that WAH improved access to quality health data by managers and this helped them manage their clinics efficiently.